How rumination influences meaning in life among Chinese high school students: the mediating effects of perceived chronic social adversity and coping style - Yu, Xiaolin; Zhao, Jingjing (Frontiers in Public Health, 2023)
Meaning in life can be affected by many factors during adolescence. This study explored the relationship between rumination and meaning in life among high school students, as well as the mediating effect of perceived chronic social adversity and coping style. A sample of 1,275 Chinese high school students were surveyed using four questionnaires. Data analysis was conducted using Harman's single-factor test, Pearson's correlation coefficient with confidence intervals (CI), and a structural equation model. We found that rumination significantly negatively affected meaning in life among high school students (β = −0.28, 95% CI = −0.33–0.23). Perceived chronic social adversity (β = −0.14, 95% CI = −0.29–0.02) and negative coping style (β = −0.09, 95% CI = −0.16–0.04) each had mediating effects between rumination and meaning in life. Further, perceived chronic social adversity and coping style had chain-mediating effects between rumination and meaning in life, with both positive (β = −0.11, 95% CI = −0.17–0.07) and negative (β = −0.08, 95% CI = −0.13–0.04) coping styles showing significant effects. To enhance the meaning in life among high school students, appropriate strategies to reduce the levels of rumination and perceived chronic social adversity are needed, while also fostering appropriate coping styles.